2015
DOI: 10.1002/anie.201505742
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Localization of RNA to Protocell Membranes by Cationic Hydrophobic Peptides

Abstract: Cooperative interactions between RNA and vesicle membranes on the prebiotic earth may have led to the emergence of primitive cells. The membrane surface offers a potential platform for the catalysis of reactions involving RNA, but this scenario relies upon the existence of a simple mechanism by which RNA could become associated with protocell membranes. Here, we show that electrostatic interactions provided by short, basic, amphipathic peptides can be harnessed to drive RNA binding to both zwitterionic phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…These include tetraalkylammonium cations binding to the exohedral surface sites of an anionic tetrahedral cage; [26] perchlorate anions occupying surface sites rather than an internal cavity site in ap entagonal-bipyramidal assembly; [27] and binding of tetraphenylborate anionst ot he exteriors urface of ac ubic cage acting to preventu ptake of smaller guests into the cavity via an allosteric effect. [28] The importance of this observation is that anys urface that combines the two properties of being both hydrophobic and cationic [29,30] may be able to act as ac atalyst for reactions of hydrophobic organic speciesw ith anionsi nasimilar way by co-location of the two reaction partners using orthogonal interactions. This combination of characteristics underpins the cation-pi interaction in water, [29] for example, and has been suggested as contributing to molecularr ecognition and catalytic processes involved in the origin of life [30] as well as molecular recognition in ar ange of supramolecular systems [31] and examples of catalysis at the surface of ionicm icelles.…”
Section: Discussionmentioning
confidence: 99%
“…These include tetraalkylammonium cations binding to the exohedral surface sites of an anionic tetrahedral cage; [26] perchlorate anions occupying surface sites rather than an internal cavity site in ap entagonal-bipyramidal assembly; [27] and binding of tetraphenylborate anionst ot he exteriors urface of ac ubic cage acting to preventu ptake of smaller guests into the cavity via an allosteric effect. [28] The importance of this observation is that anys urface that combines the two properties of being both hydrophobic and cationic [29,30] may be able to act as ac atalyst for reactions of hydrophobic organic speciesw ith anionsi nasimilar way by co-location of the two reaction partners using orthogonal interactions. This combination of characteristics underpins the cation-pi interaction in water, [29] for example, and has been suggested as contributing to molecularr ecognition and catalytic processes involved in the origin of life [30] as well as molecular recognition in ar ange of supramolecular systems [31] and examples of catalysis at the surface of ionicm icelles.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus is on molecules that are prebiotically plausible. Previous studies have shown evidence for interactions between fatty acid vesicles and nonprebiotic amino acids and peptides (23)(24)(25)(26)(27). Here, we use decanoic acid as our fatty acid rather than longer-tailed versions that produce more stable membranes but are less prebiotically plausible.…”
mentioning
confidence: 99%
“…Instead of starting from a homogeneous/chiral RNA world, there could have been a heterogeneous/chiral mixture of RNA and DNA that could have led to the accumulation of the thermally and thermodynamically more stable homochiral homogeneous RNA and DNA sequences/duplexes/structures capable of fulfilling the informational and catalytic roles necessary for Darwinian co‐evolution (Scheme ), avoiding the “prebiological necessity” for RNA to invent catalysts to give rise to DNA and the subsequent genetic takeover . Such a heterogeneous‐to‐homogeneous scenario would imply a co‐formation, co‐existence and co‐evolution of RNA and DNA, likely to be aided by the presence of other classes of molecules such as proto‐peptides and proto‐lipids …”
Section: Methodsmentioning
confidence: 99%